Pathogenesis of drug resistant epilepsy - S. M. Malyshev; T. M. Alekseeva; W. A. Khachatryan; M. M. Galagudza (Эпилепсия и пароксизмальные состояния)
Pharmacotherapy is the first-line treatment modality for epilepsy. However, in 20-40% of patients, epilepsy is resistant to pharmacotherapy. These numbers have not changed for decades despite the development and use of antiepileptic drugs with novel mechanisms of action. Drug-resistant epilepsy is now considered a separate pathophysiologic and clinical entity. The existing hypotheses on its pathogenesis could be divided in two groups. Firstly, drug-resistance might be caused by an abnormal pharmacokinetics or pharmacodynamics of antiepileptic drugs as a result of congenital or acquired dysfunction of the transporter or receptor proteins. Secondly, it might be a consequence of inherent features of epilepsy per se, such as the so-called “intrinsic severity” or some disorder of the connectome. Taking into account the complexity of this phenomenon, the issue of drug resistance continues to remain in the focus of the current research efforts.